2020
DOI: 10.1155/2020/4538135
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Outcomes of Patients with Neovascular Age-Related Macular Degeneration Treated with Aflibercept under the National Health Insurance Program in Taiwan

Abstract: Purpose. To observe and analyze the long-term outcomes of patients with neovascular age-related macular degeneration (nAMD) treated with aflibercept monotherapy under the National Health Insurance (NHI) program in Taiwan. Methods. This retrospective observational study was conducted at Taipei Veterans General Hospital. Patients with naive nAMD who were treated with aflibercept and followed for more than 3 years were reviewed. The better eye was enrolled if both eyes were affected. Visual acuity (VA) and centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The possible explanations might be as follows: The approved doses injections had to be administered within five years following the reimbursement approval under the policy of National Health Insurance reimbursement criteria for ranibizumab and aflibercept during the study period. Moreover, in recent real-world studies, [ 33 , 34 ] investigators found that most injections were given in the first four years following the initialization of intravitreal anti-VEGF treatment. This may explain the reason why the survival line of anti-VEGF agents was unchanged after 48 months, since further renal adverse effects may not be present after the termination of regular intravitreal anti-VEGF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanations might be as follows: The approved doses injections had to be administered within five years following the reimbursement approval under the policy of National Health Insurance reimbursement criteria for ranibizumab and aflibercept during the study period. Moreover, in recent real-world studies, [ 33 , 34 ] investigators found that most injections were given in the first four years following the initialization of intravitreal anti-VEGF treatment. This may explain the reason why the survival line of anti-VEGF agents was unchanged after 48 months, since further renal adverse effects may not be present after the termination of regular intravitreal anti-VEGF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we described the real-world outcomes of patients with nAMD treated with aflibercept with an average total of 8.16 ± 4.57 injections over 3 years [ 29 ]. Despite good anatomical outcomes, the average BCVA at 3-year follow-up had declined to a level below the baseline one.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, some patients do not receive sufficient anti-VEGF treatment [ 31 ]. In previous work, we concluded that in treating nAMD in a real-world setting, intensive treatment with more injections or other strategies would be required for patients that are at risk of having a poor prognosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation